2006
DOI: 10.1002/ir.170
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal and structural factors contributing to challenges in the work of the scholarship of teaching and learning

Abstract: Much progress has been made in efforts to conduct, support, value, and use the scholarship of teaching and learning in higher education. Nevertheless, to further enhance student learning, many challenges remain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 18 publications
0
42
0
5
Order By: Relevance
“…While there is research about researcher performativity and recognition, which Curtis (2008) warns risks subordinating research excellence, little has directly focused on how researchers conceive of While credibility is a relative notion (Nordhagen et al, 2014), it became clear in this study that all participants perceived credibility as aligned with the value that their SoTL research offers to the learning community. The findings highlight that credibility for SoTL researchers may well differ from institutional and external indicators of credibility (McKinney, 2006;Walker, Baepler, & Cohen, 2008). This differential provides multiple challenges for researchers since they need to address structural requirements while also trying to prioritise their own objectives.…”
Section: Implications and Conclusionmentioning
confidence: 95%
See 2 more Smart Citations
“…While there is research about researcher performativity and recognition, which Curtis (2008) warns risks subordinating research excellence, little has directly focused on how researchers conceive of While credibility is a relative notion (Nordhagen et al, 2014), it became clear in this study that all participants perceived credibility as aligned with the value that their SoTL research offers to the learning community. The findings highlight that credibility for SoTL researchers may well differ from institutional and external indicators of credibility (McKinney, 2006;Walker, Baepler, & Cohen, 2008). This differential provides multiple challenges for researchers since they need to address structural requirements while also trying to prioritise their own objectives.…”
Section: Implications and Conclusionmentioning
confidence: 95%
“…Hutchings & Shulman, 1999;Weimer, 2008). Existing literature highlights the notion that credibility is an elusive factor since it cannot be universally defined (Nordhagen, Calverley, Foulds, O'Keefe, & Wang, 2014) and can be viewed from a number of perspectives that are influenced by attitudinal beliefs and structural factors (McKinney, 2006). How one defines credibility therefore depends on perceptions of self and of one's work in relation to perceived expectations, both personal and structural.…”
Section: Abstract Credibility Of Sotl Research Valuing Of Sotl Reseamentioning
confidence: 99%
See 1 more Smart Citation
“…The Scholarship of Teaching and Learning (SoTL) is defined by many as the practice of inquiry into student learning and the teaching processes that facilitate learning, with the goal of improving both (Boyer, 1990;Felten, 2013;McKinney, 2006). In SoTL research, the classroom becomes a site of inquiry where teaching and assessment practices and approaches are often both the method and the object of study in terms of how well they facilitate student learning.…”
Section: Sotl In the Lis Classroom: Helping Future Academic Librarianmentioning
confidence: 99%
“…' (L8) If lecturers are expected to be supportive of the goals of quality teaching and student success, many authors, including McKinney (2006) and Buller (2015) have indicated that these goals might be better achieved by taking the teaching …”
Section: Counting the Opportunity Cost Of Professional Learningmentioning
confidence: 99%